Assessing Public Debt Sustainability: An Empirical Study of Nepal - Bista, Nar Bahadur (Economic Journal of Development Issues, 2010)
Public debt is increasing tremendously year by year in Nepal. The economic growth rate is very low and other macroeconomic indicators are not so encouraging. In this context, there is a question of long run sustainability of public debt. If public expenditure and public revenue are I(0) i.e. stationary public debt is sustainable but if these are I(1) i.e. nonstationary and not co- integrated the public debt is said to be unsustainable. The revenue and expenditure time series data from fiscal year 1974/75 to 2009/10 are I (1) and there is no cointegration. This exhibits that the public debt is unsustainable in Nepal. Key words: Sustainability; Stationary; Public debt; Public expenditure; Cointegration Economic Journal of Development Issues Vol. 9 and 10 (2008 & 2009) Combined Issue Page: 77-84